Baseline consumption and changes in sugar-sweetened beverage consumption and the incidence of hypertension: The SUN project. Issue 6 (December 2015) - Sayon-Orea, Carmen; Martinez-Gonzalez, Miguel A.; Gea, Alfredo; Alonso, Alvaro; Pimenta, Adriano M.; Bes-Rastrollo, Maira
Summary: Background & aims: Sugar-sweetened beverages (SSB) consumption has been associated with increased risk of cardiometabolic diseases. The association of SSB consumption with the risk of hypertension, however, has been seldom studied. Therefore, we aimed to evaluate this association. Methods: The SUN project is a Spanish cohort study of university graduates. For the present analyses we included 13, 843 participants, initially free of hypertension. Participants were followed up through mailed questionnaires. SSBs consumption was assessed at baseline and at the 6-year follow-up questionnaires. The outcome was the incidence of hypertension. To assess the relationship between categories of SSB consumption and the risk of developing hypertension during follow-up, Cox regression models were fitted. Additionally stratified by sex analysis were conducted. Results: During follow-up (median: 8.1-y), 1308 incident cases of hypertension were identified. After adjusting for potential confounders, the hazard ratio for developing hypertension among participants in the highest category (≥7 servings/week) of SSB consumption was 1.33 (95% CI:1.08–1.68) compared to those in the lowest category (non-drinkers) ( p for trend: 0.007). This association seems to be stronger among women [1.55 (95% CI:1.11–2.15) p for trend: 0.007]. As a secondary analysis, after 6-y of follow-up an increase in SSB consumption was associated with 26% higher odds of developing hypertension [OR = 1.26 (95% CI:1.02–1.55)]. Conclusion: In this Mediterranean cohort study, both higher baseline consumption (≥7 servings/week) and an increase in SSB consumption were associated with a higher risk of hypertension. However further longitudinal studies and trials are needed to confirm this association.